Spontaneous biliary perforation in a 3-month old - Vallery Logedi; Erik N. Hansen (Elsevier, 2018)
Spontaneous biliary perforation is a rare cause of jaundice in young children. A 3-month old girl presented to a referral facility with a history of jaundice and abdominal distension. Investigations suggested a hepatic cyst but on exploration, she was found to have bilious ascites and a sub-hepatic biloma consistent with spontaneous biliary perforation. Intraoperative cholangiogram demonstrated an intact biliary tree and normal duodenal drainage. Closed-suction drainage of the sub-hepatic collection alone led to complete resolution of symptoms. Keywords: Bile duct perforation, Infant, Jaundice, Spontaneous biliary perforation